THE EFFECT OF JOB GUIDANCE TRAINING ON THE PRODUCTIVITY OF PRISONERS IN THE CLASS I PENITENTIARY IN MEDAN - Manurung, Muhammad Rizki; Rachmayanthy, Rachmayanthy (Universitas Nusa Cendana, 2025)
This research will go in depth on the effect of job guidance training on the productivity of prisoners at the Medan Class I Penitentiary. This research aims to provide a clearer picture of the role of job guidance training in achieving the goals of inmate rehabilitation at the Medan Class I Penitentiary. This research uses quantitative research methods, using IBM SPSS version 26.0 software to test the data that has been obtained. Based on the results of data analysis, there is an influence of job training guidance on employee productivity at the Medan Class I Correctional Institution. Keywords: Training; Work Productivity; Prisoners